The Abundance of Plasmid-Mediated Quinolone Resistance Genes in Enterobacter cloacae Strains Isolated from Clinical Specimens in Kermanshah, Iran - Mandana Afsharian; Somayeh Asadi; Camellia Danesh; Reza Sedighi; Kohsar Karimi; Nooshin Miladi; Ronak Miladi; Mohsen Azizi; Nahid Madadi-Goli; Kamal Ahmadi; Mohammad Hossein Zamanian (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Enterobacter cloacae (E. cloacae) is one of the most common Enterobacteriaceae causing nosocomial infections. Plasmid-mediated quinolone resistance (PMQR) determinants have been considered recently. This study evaluated the abundance of PMQR genes in strains of E. cloacae obtained from clinical samples in Kermanshah, Iran. Methods. In this descriptive cross-sectional study, after collecting 113 isolates of E. cloacae, their identity was confirmed using specific biochemical tests. After determining their drug resistance patterns using disc diffusion, the phenotypic frequency of extended-spectrum beta-lactamase (ESBL)-producing isolates was measured by the double-disk synergy test (DDST) method. The isolates were examined for the presence of qnrA, qnrB, qnrS, and aac(6′)-Ib-cr genes by the polymerase chain reaction (PCR) assay. Results. The antibiotic resistance rate of E. cloacae isolates varied from 9.7% to 60.2%; among them, 78% were multidrug-resistant (MDR). The highest quinolone resistance was observed in ESBL-producing strains of E. cloacae. The frequency of positive isolates for PMQR and ESBL was 79.6% and 57.5%, respectively. The genes aac(6′)-ib-cr (70.8%) and qnrB (38.1%) had the highest frequency among other genes. The number of isolates simultaneously carrying 2 and 3 genes was 64 and 5 isolates, respectively. Conclusion. The obtained results indicate a high degree of quinolone resistance among ESBL-producing E. cloacae strains. Nevertheless, there was a significant relationship between the PMQR gene and ESBL-positive isolates. Therefore, special attention should be paid to molecular epidemiological studies on antibiotic resistance to quinolones and beta-lactamases in these strains.